Commonest Type of Congenital Heart Disease (CHD) Among Children in Maternity and Children Hospital (MCH) - Mansour Ahmed Mohammed Almakrami, Nasser Mesfer Rashed AL-Abataheen, Abdullah Saleh Alyami; Mohammed Yahia Hassan Alyami, Ibrahim Awad Mohdi Alyami, Khalid Hamad Hussein Alsalem; Abdulrhman Ali Alyami, Mahdi Yahia Alzamanan, Fahad Ahmed Ali Alkanfari; Mohammad Al Abbas, Obaid Mahdi (International Journal of Innovative Research in Medical Science, 2017)
CHD means a child is born with an abnormally structured heart and/or large vessels. Such hearts may have incomplete or missing parts, may be put together the wrong way, may have holes between chamber partitions or may have narrow or leaky valves or narrow vessels(1). It has two types cyanotic and acyanotic. (2) facility- based descriptive case series study including qualitative research approaches study will be conducted in Maternity and Children's Hospital in Najran to assess patients with CHD from neonatal period to two years old from (1)- 1436 H to (9) – 1436 H. sampling non-probability sampling by using the purposive and convenience techniques. The data will be collected by structured the check lists. Data processing and analysis will be done by entering the data into SPSS for Windows. After analyze of data the commonest type of congenital heart disease is atrial septal defect as percent 27.27% followed by ventricular septal defect as percent 18.18%. The consanguinity marriage has a relationship with congenital heart disease as it is effect 68.2% and just 31.8% are not affected.